Human Rights Violation in Conflict Zones: A case study of Bodoland. - Rahman, Mofidur (International Journal of Psychosocial Rehabilitation, 2020)
Assam is a conflict prone zone. The state has witnessed several kinds of ethnic and communal violence over the decades. The Bodoland also witnessed several forms of violence since 1993. The magnitude of the violence is very wretched and brutal. As a result of this violence there was violation of human rights including the rights of women and children. However, a terror activity like extortion, bombing, kidnapping, by insurgent groups has become a normal phenomenon in Bodoland. From 1993 to 2012 there are six brutal violence occurred in Bodoland which makes Bodoland a living hell in the earth. In the recent Bodoland violence more than 150 peoples have lost their life; 5 lakhs people have been displaced and made homeless by the miscreant. Besides, a huge amount of property like houses, schools, religious establishments has been destroyed. However, it is noteworthy to mention that the role of government during the violence was not satisfactory. The state has failed to address the problem of the Bodoland. It has also failed to protect life, liberty and property of the citizens and failed to promote and protect human rights as well. Therefore, in this critical juncture it’s imperative to address the issues relating to human rights violation.